(untitled) (Nepalese Journal of Management Research, 2025)
The purpose of this study is to examine factors that can serve as a means to reduce staff turnover in Nepalese organizations. This study employed a survey research design, with the unit of analysis comprising employees from ten Nepalese business organizations, including four commercial banks, three finance companies, and three life insurance companies. Data were gathered using standardized 6-point Likert scale questionnaires. A total of 225 participants were involved in this study and their responses were used for data analysis purposes. The findings indicate that improved compensation policies, high levels of job satisfaction, robust career growth opportunities, increased motivation, and a positive work environment all contribute to prevent staff turnover. Therefore, Nepalese business organizations should prioritize these factors to retain their workforce and reduce turnover intentions. Moreover, employing the best candidates, providing competitive pay, encouraging work-life balance, identifying and rewarding hard work, establishing clear career paths, evaluating historical turnover data, offering flexible scheduling, improving employee engagement, and putting in place efficient human resource development (HRD) procedures are all ways to reduce staff turnover.